The impact of Sanming’s healthcare reform on medical resource misallocation: based on synthetic control method - Guo, Lin; Fan, Chengxin; Yang, Chunxiao; Ma, Dongping; Sun, Kui; Sang, Xingang; Chen, Zhongming; Guo, Hongwei; Yin, Wenqiang (Frontiers in Public Health, 2025)
BackgroundThe global misallocation of healthcare resources has emerged as a critical impediment to public health. In China, healthcare resources are predominantly concentrated in major cities and high-tier hospitals, while primary care facilities suffer from inadequate capacity, contributing to issues such as “difficult and expensive access to healthcare.” Despite numerous healthcare reforms, significant disparities in resource distribution persist.ObjectiveThis study seeks to elucidate the causal effects of healthcare system reform on the misallocation of medical resources and to investigate the underlying mechanisms. Focusing on the healthcare reform implemented in Sanming in 2012 as a quasi-natural experiment, the research employs the synthetic control method (SCM) to assess the policy’s impact on resource misallocation.MethodsThe synthetic control method is applied to estimate the causal impact of the Sanming Medical Reform on the misallocation of healthcare resources. By constructing a weighted control group that replicates Sanming’s counterfactual resource allocation trajectory in the absence of the reform, the model controls for covariates such as industrial structure, GDP, and human resources to ensure precise estimation of the policy effect. Data were obtained from the National Bureau of Statistics, local health commissions, and other sources, forming a balanced panel dataset of 203 cities spanning 2007 to 2022.ResultsThe analysis reveals that the Sanming Medical Reform markedly reduced the misallocation of healthcare resources. Following the 2012 intervention, Sanming exhibited a substantial decline in misallocation, with the misallocation index decreasing by an average of 0.1412 between 2013 and 2017. Both city-level and time placebo tests confirm that the observed policy effect is statistically significant and not attributable to random variation. Mechanism analysis further indicates that the reform achieved its outcomes by increasing government expenditure on health and refining the structure of health insurance.ConclusionThe empirical evidence demonstrates that the Sanming Medical Reform effectively alleviated the misallocation of healthcare resources and bolstered primary care capacity through enhanced government spending and optimized health insurance payment structures. These findings offer valuable insights and empirical support for healthcare reforms in China and other countries, paving the way for more equitable and efficient resource allocation.